Notes on behaviour of Ruddy Ducks during the brood period - Siegfried, W Roy (Wildfowl, 1977)
Only female Ruddy Ducks Oxyura jamaicensis accompanied broods. Maternal vocalization and injury feigning are reported. Females remained with their broods until the young were at least four weeks old. Broods older than four weeks were less cohesive than young ones. Broods seldom foraged in emergent vegetation. Two females moulted their remiges while accompanying broods.